Geometry of wheel–rail contact: extended envelope method. (5th August 2014) - Decuyper, M.
This paper proposes a general method for determining the wheel–rail contact point based on the principles of M. Bouteloup's 'envelope method'. The method enables the contact points of a wheelset on a track to be determined, without any restriction to close–to–nominal state. Consequently it also allows to detect and to localize a double wheel rail contact, located on the flange and on the tread. Numerical results of this method are given and commented, in a case of general wheel and rail profiles.